Olympiodori in Platonis Gorgiam commentaria - Olympiodorus; Westerink, Leendert Gerrit; Deutsche Akademie der Wissenschaften zu Berlin. Zentralinstitut für Alte Geschichte und Archäologie. (Leipzig : B.G. Teubner, 1970)
Olympiodori Philosophi in Platonis Gorgiam Commentaria (Bibliotheca Scriptorum Graecorum et Romanorum Teubneriana).
Includes bibliographical references and indexes.
eBooks on EBSCOhost
Keywords: Plato; Phaedo (Plato); POETRY -- Epic